IDENTIFIKASI GERONGGANG (Cratoxylon arborescens (Vahl.) Blume ) TERHADAP KRASIKARPA (Acacia crassicarpa A. Cunn.): Identification of Geronggang (Cratoxylon arborescens (Vahl.) Blume) on Krasikarpa (Acacia crassicarpa A. Cunn.) by Kemometrik Methods - Hadi, Samsul; Adi, Rahmadi; Rahayu, Setyawati (Jurnal Penelitian Hasil Hutan, 2024)
Raw materials for making paper concern the government, especially when dealing with peat environments. One of the paper-making materials that lives in peat environments is Cratoxylon arborescens (Vahl.) Blume, so the research aims to identify Cratoxylon arborescens (Vahl.) Blume against the risk of being mixed with Acacia crassicarpa A. Cunn. So, it can be used to identify paper raw materials. The method used in this research uses principle component regression (PCR). The materials used are Cratoxylon arborescens (Vahl.) Blume wood sticks, Cratoxylon arborescens (Vahl.) Blume and methanol p.a. The equipment used is spectrophotometry. The results showed two wavelength areas, 212–236 nm and 265–302 nm, which can potentially obtain optimal RMSEC, RMSEP, and RMSECV values for identifying the peak areas of the two species. This research concludes that the 212 – 236 nm area can potentially identify Cratoxylon arborescens (Vahl.) Blume with RMSEC: 4.98; RMSEP: 2.91 and RMSECV: 8.13.